The Reliability and Variability of Three-dimensional Tibial Acceleration During Running - Sheerin, K; Besier, T; Reid, D; Hume, P (University of Konstanz Library, 2016)
Axial and resultant peak tibial acceleration might be useful for screening/monitoring runners at risk of lower limb injury. This study quantified between-session reliability and variability of axial and resultant peak tibial acceleration during running. Fourteen runners completed four running speeds at two testing sessions seven days apart with tri-axial wireless accelerometers attached to the tibia. Average mean differences between sessions across all four speeds (for the right or left side) were 4.5-5.7% (ES 0.01-0.17; ICC 0.73-0.95; CV% 7.5-1 7.9) for axial and 0.9-5.1 % (ES 0.01 -0.1 2; ICC 0.84-0.97; CV% 5.913.9)) for resultant peak tibial acceleration. While both axial and resultant peak tibial acceleration are reliable and therefore appropriate for monitoring and assessment of an intervention, resultant peak tibial acceleration should be preferentially used.
Keywords: Screening; Monitoring; Resultant; Between-day